IKTIODIVERSITAS DI SUNGAI WANGGO KAMPUNG ERAMBU DISTRIK SOTA KABUPATEN MERAUKE - Edmondus K. Laratmase; Norce Mote; Edy HP. Melmambessy (Musamus Fisheries and Marine Journal, 2019)
This study aims to determine the diversity of fish in the River Wanggo District Sota Merauke regency. This research was conducted in May-July 2017. The method used in this research is The method used is survey. Data analysis used are Species Wealth, Diversity Index (H'), Evenness Index (E), Domination Index (D). The results of the study there are 25 species of fish with a total catch of 1,392 tails. The index value of Diversity (H ') and moderate (1.10-1.27) whereas fairness values ​​are high (2.39-2.72) and the spread of each species is evenly distributed. No fish dominates all three stations. Keywords: Ichtiyodiversity; Wanggo River; Merauke.